Global Picture of Genetic Relatedness and the Evolution of Humankind - Khvorykh, Gennady V. (Biology (Basel), 2020)
SIMPLE SUMMARY: The intricacies of human ancestry are buried deep within our DNA. For years, scientists have been working to piece together a vast picture of our genetic lineage. The purpose of this study was to further reveal this global picture of human genetic relatedness using identical-by-descent (IBD) genomic fragments. We processed over 65 million very rare single nucleotide polymorphic (SNP) alleles and detected over 17 million shared IBD fragments, including very short IBD fragments that allowed us to trace common ancestors back to 200,000 years ago. We also determined nine geographical regions representing nine unique genetic components for mankind: East and West Africa, Northern Europe, Arctica, East Asia, Oceania, South Asia, Middle East, and South America. The levels of admixture in every studied population could be assigned to one of these regions and long-term neighboring populations are strikingly similar, despite any political, religious, and cultural differences. Additionally, we observed the topmost admixture to be in central Eurasia. The entire picture of relatedness of all the studied populations presents itself in the form of shared number/size of IBDs, providing novel insights into geographical admixtures and genetic contributions that shaped human ancestry into what it is today. ABSTRACT: We performed an exhaustive pairwise comparison of whole-genome sequences of 3120 individuals, representing 232 populations from all continents and seven prehistoric people including archaic and modern humans. In order to reveal an intricate picture of worldwide human genetic relatedness, 65 million very rare single nucleotide polymorphic (SNP) alleles have been bioinformatically processed. The number and size of shared identical-by-descent (IBD) genomic fragments for every pair of 3127 individuals have been revealed. Over 17 million shared IBD fragments have been described. Our approach allowed detection of very short IBD fragments (<20 kb) that trace common ancestors who lived up to 200,000 years ago. We detected nine distinct geographical regions within which individuals had strong genetic relatedness, but with negligible relatedness between the populations of these regions. The regions, comprising nine unique genetic components for mankind, are the following: East and West Africa, Northern Europe, Arctica, East Asia, Oceania, South Asia, Middle East, and South America. The level of admixture in every studied population has been apportioned among these nine genetic components. Genetically, long-term neighboring populations are strikingly similar to each other in spite of any political, religious, and cultural differences. The topmost admixture has been observed at the center of Eurasia. These admixed populations (including Uyghurs, Azerbaijanis, Uzbeks, and Iranians) have roughly equal genetic contributions from the Middle East, Europe, China, and India, with additional significant traces from Africa and Arctic. The entire picture of relatedness of all the studied populations unfolds and presents itself in the form of shared number/size of IBDs.